Amaranthus viridis L. as alternative treatment for hypercholesterolemia and atherosclerosis - Salvamani, Shamala (2016)
Inflammation and oxidative stress are involved in the pathology of several chronic diseases including hypercholesterolemia and atherosclerosis. Oxidized low density lipoprotein (LDL) accumulation leads to atherosclerotic plaque formation, which contributes to myocardial infarction and cardiovascular diseases. Synthetic drug,statins, causes adverse effects on liver and muscles, thus 3-hydroxy-3-methylglutarylcoenzyme A (HMG-CoA) reductase inhibitors from plant origin are needed.Amaranthus viridis (A. viridis) has been used for its medically beneficial properties from ancient time. Thus, the focus of this study was on A. viridis leaf extract; its phytochemicals, safety, antioxidant, anti-inflammatory, hypocholesterolemic and antiatherosclerotic properties. In this study, the different parts of A. viridis (leaf, stem and seed) were evaluated for anti-HMG-CoA reductase activity. A. viridis leaf extract showed the highest inhibitory effect, about 72%.Therefore, A. viridis leaf extract was examined in order to investigate its phytocomponents. Gas chromatography-tandem mass spectrometry (GC-MS/MS) analysis detected 30 compounds while reverse phasehigh performance liquid chromatography (RP-HPLC) revealed the presence of ascorbic acid, rutin, quercetin and catechin. In vitro cytoxicity effect of A. viridis extract was estimated using sulforhodamine B (SRB) assay on Vero and WRL-68 cells lines. SRB assay revealed non cytotoxic effect of A. viridis with IC50 value of more than 1000 μg/ml. Acute and subchronic toxicity study in rats for 14 and 90 days, respectively,showed no significant elevation in biochemical and haematological parameters compared to the control group. Histopathological examination revealed no harmful effects observed in heart, lung, liver,kidneys and spleen. Cytotoxicity, acute and subchronic toxicity studies confirmed that A. viridis extract is non toxic and can be utilized as a therapeutic agent. The antioxidant and anti-inflammatory activities of the extract were analyzed in various in vitro assays. A. viridis extract exhibits high antioxidant activity in inhibiting radicals like hydroperoxides, 2,2-diphenyl-1- picrylhydrazyl (DPPH), nitric oxide (NO) and ferric ions. Anti-inhibitory activity of A.viridis extract on hyaluronidase, xanthine oxidase and lipoxygenase enyzmes revealed a desirable anti-inflammatory properties. The experimental data indicated that A. viridis leaf is a potent antioxidant and anti-inflammatory agent. Animal model study was performed on twenty New Zealand white rabbits that were randomly divided into 5 groups and fed with normal diet, 2% high cholesterol diet (HCD), 2% HCD + 10 mg/kg simvastatin, 2% HCD + 100 mg/kg A. viridis extract and 2% HCD + 200 mg/kg A.viridis extract, respectively. The supplementation with A. viridis extract significantly reduced total cholesterol, LDL and triglycerides levels, and increased high density lipoprotein (HDL) and antioxidant enzymes [superoxide dismutase (SOD) and glutathione peroxidase (GPx)] levels. The elevated levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatine kinase (CK) in hypercholesterolemic control and simvastatin-treated groups indicate liver and muscle injuries. Treatment with A. viridis extract also diminished the development of aortic plaque and decreased the intima: media ratio as observed in simvastatin-treated rabbits. The in vivo study on A. viridis leaf extract further confirms its potential as an alternative therapeutic agent for hypercholesterolemia and atherosclerosis.